Enhancing Employability and Empowerment: Unveiling Factors within PERDA-TECH for Sustainable Development - Ahmad, Siti Rozaini; Isa, Nurulhuda; Liaw, Annie; Nazari, Muhammad Luqman; Abdullah, Nor Paezah; Rani, Mohd Husaini; Ahmad, Anizana; Abd Rahman, Abd Qayyum; Mohd Lokman, Anitawati (Journal of Technical Education and Training, 2023)
In the contemporary landscape of education, fostering graduates' employability has emerged as a vital concern for educational institutions and policy makers, particularly within the framework of Sustainable Development Goal 4 (SDG4) and Sustainable Development Goal 8 (SDG8). This paper delves into the employability dynamics of graduates from the PERDA-TECH program, a Technical and Vocational Education and Training (TVET) initiative operating under the auspices of the Penang Regional Development Authority (PERDA). In the quest for a competitive edge within the workforce, TVET programs hold the promise of cultivating a skilled labor pool that aligns with the workforce demands, thus bolstering economic growth (SDG8). However, a comprehensive analysis of the graduate employability facets is indispensable to address the nuanced requirements of the job market. Existing studies have outlined seven pivotal employability skills, encompassing interpersonal skills, critical thinking, self-improvement, resourcefulness, ICT proficiency, fundamental aptitudes, and information literacy. Additionally, employers place premium emphasis on attributes such as social acumen, management proficiencies, creative thinking, problem-solving capabilities, and critical analysis. Aligned with these imperatives, the PERDA-TECH Malaysia Skills Training Programme seeks to equip graduates with competencies tailored to amplify their employability prospects. Nonetheless, the insights from the PERDA 2020 Outcome Assessment report reveal a gap in the comprehensive understanding of graduate feedback and employability determinants. This study endeavors to bridge this gap by methodically examining the factors influencing graduates' employability within the PERDA-TECH program. Employing a quantitative approach, the study encompassed survey responses from 226 graduates. The findings unveiled a noteworthy 71.3% (162 graduates) employed, 21.2% (48 graduates) pursuing further education, and 7.1% (16 graduates) currently unemployed. Encouragingly, a significant proportion of graduates secure employment within six months of graduation, substantiating the program's efficacy in catering to market needs (SDG8). The factors influencing employability were dissected into three categories: graduate attributes, learning outcomes, and market dynamics. This holistic analysis enhances the alignment of the program's objectives with SDG4's emphasis on quality education and SDG8's pursuit of decent work and economic growth. This study underscores the symbiotic relationship between relevant and skill-centered education, graduates' market readiness, and sustainable economic development. As a result, it contributes not only to the advancement of knowledge but also to the realization of SDG4 and SDG8, enlivening the overarching mission of fostering inclusive education and propelling economic progress.